This tickles beyond all measure: an expanded version of Henning's Hieb-Fechten in Add MS 17533 - van Noort Reinier (Bern Open Publishing, 2019)
Erhardus Henning's work on Hieb-Fechten is one of only a few 17th century German fencing treatises describing cut-based fencing. An expanded version of this text, containing a larger collection of lessons, can be found in British Library Add MS 17533 fol. 127v to 138v, titled only Daß Hieb Fechten. Based on the great similarities between these two texts, it is clear that they share a common ancestor.